Multimodal repair of renal artery aneurysm: 10-year single center experience - Abbasi Dezfouli, Sepehr; Ramouz, Ali; Demirel, Serdar; Chang, De-Hua; Mehrabi, Arianeb; Böckler, Dittmar (Annals of vascular surgery, 2022)
Background - Renal artery aneurysm (RAA) is a rare disease with various treatment options in indicated patients. In the current survey, the 10-year experience in treatment of RAAs using different endovascular and surgical treatments depending on RAA characteristics is discussed. - Methods - All patients undergone RAA treatment via endovascular or surgical approaches at our center between January 2010 and December 2020 were enrolled. Patient demographics and peri-operative and late results were collected from a prospectively maintained database. - Results - Eleven patients with RAA underwent treatment as follows: 4 patients received endovascular approach, 4 patients underwent in-situ RAA repair, and kidney autotransplantations were carried out in 3 patients. In all three treatment groups, the first therapeutic attempt was successful and none of the patients underwent secondary intervention due to RAA. Kidney autotransplantation was associated with a higher blood loss and a longer time of procedure compared to that of endovascular approach and in-situ repair. In-hospital postoperative complications were reported in 5 patients, including renal pole perfusion defect, renal artery thrombosis, and urinary tract infection. No acute kidney organ loss was seen, but 1 patient suffered from chronic kidney loss due to renal artery occlusion. In 1 patient undergoing autotransplantation, ureter anastomosis was reported, which led to acute renal failure, and a surgical treatment with resection and reanastomosis of the ureter was necessary. Hypertension was not resolved after RAA repair in any of the patients with preoperative hypertension. - Conclusions - RAA treatment selection depends on patient characteristics, anatomy, location, and arising branches of the aneurysm. In cases with complex anatomy, treatment strategy could not be just decided based on consensus guidelines, but a multidisciplinary team is required. Interventional therapies showed excellent results in non-complicated proximal aneurysms, especially regarding the length of hospital stay and postoperative morbidities. Open surgery is a complementary alternative in cases where minimally invasive therapy is not possible. Ex-situ repair with autotransplantation could be considered for anatomically complex distal aneurysms.